Deixis Study in Speech Text of President Joko Widodo on Independence Day - Kresna Ningsih Manik; Merry Susanty Br. Tarigan; Dolli Rotua Sinaga (UIN Salatiga, 2023)
The deixis in the speech text of President Joko Widodo on Independence Day, August 17, 2022, is the subject of this article. This study's objectives are to identify deixis types, identify the dominant type in the speech text of President Joko Widodo, and explain deixis types and their causes. The study aims to identify the prevalent deixis type, understand the procedure, and determine why President Joko Widodo uses deixis in his speeches. This study employs the qualitative content analysis research design. The speech text of President Joko Widodo on Independence Day, August 17, 2022, serves as the data's primary source. The documentary technique is used for data collection. Documentary sheets are the tool used for data collection, and content analysis is the method used for data analysis. President Joko Widodo's speech text analysis on Independence Day reveals five different types of deixis. According to the analysis, social deixis is the most frequently used. The purpose of social deixis in a speech for Independence Day by President Joko Widodo demonstrates that there are distinctions in the roles of recipients of speech referrals and revealed reveals language politeness tactics, particularly those related to cultural factors, and depicts how a person's social status, such as age, occupation, education background, and social position, impacts a country's leader to deliver his Speech during the celebration of Independence Day.